Fatherless in matrilineal societies: a quantitative profile from the Minangkabau context and its implications for culturally responsive counselling - Triave Nuzila Zahri; Ade Herdian Putra; Lisa Putriani; Muvi Yandra; Firdha Ainil Hakim (Journal of Counseling, Education and Society, 2026)
This cross-sectional quantitative study examined perceived fatherless among 488 adolescents in Padang, West Sumatra, within the Minangkabau matrilineal cultural context. Participants were recruited via convenience sampling from 169 school units and responded to a validated 20-item Fatherless Scale grounded in the tripartite model of father involvement (Cronbach's alpha = 0.788; Aiken's V = 0.67–0.92). Descriptive statistics and t-SNE dimensionality reduction with K-Means cluster analysis were used to map the distribution and latent structure of perceived paternal involvement. Results showed that 53.9% of respondents fell within the very low and low categories of perceived father involvement, despite 79.9% living with both parents and 90.0% having a living biological father. These categories were operationally defined using M ± SD boundaries; the categorical framework served as a descriptive reporting tool, while t-SNE and cluster analysis independently confirmed that the underlying response structure constitutes a gradient continuum rather than discrete groups. Adolescents living with both parents reported the lowest mean involvement (M = 40.59) compared to single-parent adolescents (M = 49.80), confirming that fatherless in this sample is predominantly a psychological and relational phenomenon rather than one of physical separation. Findings carry direct implications for culturally responsive counseling within Minangkabau family systems.